Pengaruh Lingkungan Kerja Fisik Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Lafiye Mode Indonesia Di Jakarta Timur - Fitriyani, Delya; Guruh, Muhamad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine the effect of the Physical Work Environment and Work Motivation on employee performance at PT. Lafiye Mode Indonesia in East Jakarta. This research is quantitative with a descriptive approach. The population in this study was all 60 employees of PT. Lafiye Mode Indonesia. The sampling technique used saturated sampling, therefore all 60 employees of PT. Lafiye Mode Indonesia were sampled in this study. The analytical methods used in data processing included validity and reliability tests, simple linear regression, multiple linear regression, correlation coefficient tests, coefficient of determination tests, and hypothesis testing (t-test and f-test) using SPSS version 25. The results of this study indicate that there is an influence between the Physical Work Environment (X1) on Employee Performance (Y) at PT. Lafiye Mode Indonesia. This can be seen from the calculated t-value of 11.845 > t-table 2.002, thus the calculated t-value > t-table with a significance value of 0.000 < 0.05. So it can be concluded that Ho1 is rejected and Ha1 is accepted. Then there is also an influence between Work Motivation (X2) on Employee Performance (Y) at PT. Lafiye Mode Indonesia, this can be seen from the results of the t-test with a calculated t value of 10.834> t table 2.002, so the calculated t> ttable with a significant value of 0.000 <0.05. So it can be concluded that Ho2 is rejected and Ha2 is accepted. And thirdly, there is an influence between the Physical Work Environment (X1) and Work Motivation (X2) on Employee Performance (Y) at PT. Lafiye Mode Indonesia in East Jakarta, this can be seen from the multiple regression equation, namely Y = 16.138 +0.138 X1 + 0.227 X2. And the results of the f-test with a calculated F value of 87.251> F table 3.159 with a significant value of 0.000 <0.05, so Ho3 is rejected and Ha3 is accepted.